Can an axion be the dark energy particle? - Elias C. Vagenas (Kuwait Journal of Science)
Following a phenomenological analysis done by the late Martin Perl for the detection of the dark energy, we show that an axion of energy $1.5\times 10^{-3}~eV/c^2$ can be a viable candidate for the dark energy particle. In particular, we obtain the characteristic length and frequency of the axion as a quantum particle. Then, employing a relation that connects the energy density with the frequency of a particle, i.e., $\rho\sim f^{4}$, we show that the energy density of axions, with the aforesaid value of mass, as obtained from our theoretical analysis is proportional to the dark energy density computed on observational data, i.e., $\rho_{a}/\rho_{DE}\sim \mathcal{O}(1)$.